Job Satisfaction for Administrative Employees in Educational Helwan Administration Of Cairo Governorate and its Relationship with Customers Satisfaction - Kotb, Salwa (The Arab Journal of Administration, 2019)
This study aims to explore the job satisfaction degrees acquired by administrative employees in educational Helwan management and to explore the customers satisfaction degrees acquired by dealers with them (teachers, parents, Mentors, managers). As this study aims to recognize the relationship between job satisfaction and customers satisfaction , the study also aims to find out whether there were statistically significant differences in the degrees of job satisfaction levels due to some demographic variables (Academic Qualifications, Job Title, experience, age). To achieve those purposes The researcher, use the descriptive method, as The study sample consisted of (158) male and female employees, it has been taken at random from within educational Helwan management, and (158) of customers it has been taken with a stratified sample of clients. The researcher prepared two questionnaires to measure both: job satisfaction and customers satisfaction from his own preparation and determination. The results were found: 1- Both of the degrees job satisfaction and customers satisfaction were generally moderate. 2- There were significant relationships between the job satisfaction degrees and customers satisfaction degrees 3- There were significant differences in job satisfaction to the variables of (Academic Qualifications, Job Title, experience and there were no significant differences in the degrees of job satisfaction due to the variable (age).